Firm listing status and the investment home bias - Dougal, Casey; Rettl, Daniel A. (Journal of Corporate Finance, 2021)
Are public firm investment rates more sensitive than private firm rates to new investment opportunities? We offer a new explanation for differences in public and private firm investment sensitivities: investment sensitivities differ because the type of investments favored by firms varies with their listing status. Specifically, we consider the geography of investment opportunities and find that private firms have a much stronger investment home-bias than similar public firms which makes their investment decisions more sensitive to local investment opportunities than public firms. Controlling for local investment opportunities explains four-fifths of the differential sensitivity between public and private firms not explained by more traditional measures of investment opportunities.